ANALISIS DAMPAK PERUBAHAN PERATURAN PAJAK TERHADAP STRATEGI PERENCANAAN PAJAK PERUSAHAAN: STUDI EMPIRIS TAHUN - Situmorang, Marlina (JURNAL NERACA, 2023)
This study aims to see the effect of tax planning, tax avoidance and corporate governance on company value in companies. This analysis model uses multiple linear regression analysis. The method used is a quantitative research method. The results of the study indicate that tax planning and corporate governance have a positive effect on company value, tax avoidance has no effect on company value and simultaneously tax planning, tax avoidance and corporate governance have a significant effect on company value. Companies that carry out efficient tax planning, proper tax avoidance and good corporate governance will generate high company profits so that the company value will increase.